Prevalence of Geriatric Syndromes in Elderly Undergoing Chemotherapy - Rizka, Aulia; Helda, Helda; Prasetyawaty, Findy; Hanjani, Arcita (UI Scholars Hub, 2022)
Introduction. Geriatric syndromes is associated with poor survival, poor quality of life and increased chemotoxicity risk in elderly receiving chemotherapy. Geriatric syndromes is currently not routinely evaluated in pre-chemotherapy clinical setting. This study aimed to identify the prevalence of some geriatric syndromes in elderly patients undergoing chemotherapy.Methods. This study is part of primary study investigating geriatric syndromes in elderly with cancer. A descriptive cross sectional study during March 2020 – March 2021 was conducted to elderly patients before chemotherapy administration in Cipto Mangunkusumo Hospital, a national referral hospital in Jakarta. Patients were recruited consecutively. Patients underwent Comprehensive Geriatric Assesment (CGA), including nutritional, depression, sarcopenia risk assessment, frailty, cognitive assessment, as well as medication review.Results. Total of140 elderly subjects were recruited with mean age of 66 years old. 52% subjects were women and 67% with solid tumor. As many as 80% subjects were having malnutrition, 40,6% were frailt, 40,3% were at high risk of sarcopenia, 14,1% with depression, and 19,1% were having cognitive impairment. Of all subjects, 24,1% have more than 3 diagnosis of geriatric syndromes.Conclusion. As geriatric syndromes are prevalent among elderly subjects receiving chemotherapy, routine identification would be useful to improve cancer treatment result.